Product market reforms and productivity : a review of the theoretical and empirical literature on the transmission channels - Nicodeme, Gaetan; Sauner-Leroy, Jacques-Bernard.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
Product market reforms are structural reforms of microeconomic type that aim at improving the functioning of product markets by increasing competition amongst producers of goods and services. Theoretical models suggest that regulation and reforms which liberalise or improve the functioning of markets can positively affect productivity through three different channels, namely • a reallocation of scarce resources (allocative efficiency), • an improvement in the utilisation of the production factors by firms (productive efficiency) and • an incentive for firms to innovate to move to the modern technology frontier (dynamic efficiency). This paper reviews the theoretical and empirical literature on these three channels.
Internal paper
Economic Papers